Glutamate metabolism in cerebral mitochondria after ischemia and post-ischemic recovery during aging: relationships with brain energy metabolism - Ferrari, Federica; Gorini, Antonella; Hoyer, Siegfried; Villa, Roberto Federico (Journal of neurochemistry, 2018)
Glutamate is involved in cerebral ischemic injury, but its role has not been completely clarified and studies are required to understand how to minimize its detrimental effects, contemporarily boosting the positive ones. In fact, glutamate is not only a neurotransmitter, but primarily a key metabolite for brain bioenergetics. Thus, we investigated the relationships between glutamate and brain energy metabolism in an in vivo model of complete cerebral ischemia of 15 min and during post-ischemic recovery after 1, 24, 48, 72, and 96 h in 1-year-old adult and 2-year-old aged rats. The maximum rates (Vmax) of glutamate dehydrogenase (GlDH), glutamate-oxaloacetate transaminase, and glutamate-pyruvate transaminase were assayed in somatic mitochondria (FM) and in intra-synaptic ‘Light’ mitochondria and intra-synaptic ‘Heavy’ mitochondria ones purified from cerebral cortex, distinguishing post- and pre-synaptic compartments. During ischemia, none of the enzymes were modified in adult animals. In aged ones, glutamate-oxaloacetate transaminase was increased in FM and GlDH in intra-synaptic ‘Heavy’ mitochondria, stimulating glutamate catabolism. During post-ischemic recovery, FM did not show modifications at both ages while, in intra-synaptic mitochondria of adult animals, glutamate catabolism was increased after 1 h of recirculation and decreased after 48 and 72 h, whereas it remained decreased up to 96 h in aged rats. These results, with those previously published about Krebs’ cycle and Electron Transport Chain (Villa et al., [2013] Neurochem. Int. 63, 765-781), demonstrate that: (i) Vmax of energy-linked enzymes are different in the various cerebral mitochondria, which (ii) respond differently to ischemia and post-ischemic recovery, also (iii) with respect to aging.
Gesehen am 19.05.2020